2004
DOI: 10.1097/01.mlg.0000149442.22393.e2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors in Well‐Differentiated Thyroid Carcinoma

Abstract: WDTC is associated with a significant recurrence rate but good disease-specific survival. The most important prognostic factors are family history of WDTC, extent of surgical treatment (i.e., total thyroidectomy), and advanced initial stage of disease, with a trend for age 60 years and older.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
3
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 12 publications
(24 reference statements)
3
50
3
1
Order By: Relevance
“…have an outcome (5-yr OS of 60%) that was intermediate between that of the overall indolent, welldifferentiated papillary and follicular carcinomas (98% OS at 10 years) 13 and the highly lethal anaplastic carcinoma (0% OS at 5 years). 8 PDTC defined mainly on the basis of growth pattern (such as the tumors reported in the large Italian study by Volante et al 8 ) also occupy an intermediate position at the prognostic level on the spectrum of thyroid carcinoma progression.…”
Section: Discussionmentioning
confidence: 97%
“…have an outcome (5-yr OS of 60%) that was intermediate between that of the overall indolent, welldifferentiated papillary and follicular carcinomas (98% OS at 10 years) 13 and the highly lethal anaplastic carcinoma (0% OS at 5 years). 8 PDTC defined mainly on the basis of growth pattern (such as the tumors reported in the large Italian study by Volante et al 8 ) also occupy an intermediate position at the prognostic level on the spectrum of thyroid carcinoma progression.…”
Section: Discussionmentioning
confidence: 97%
“…ETE is defined as extension of the primary tumor outside of the thyroid capsule with invasion into the surrounding structures (35). Gross ETE has been identified as carrying a higher risk for local recurrence (36,37) and is used in several staging systems, including TNM (tumor, node, and metastasis) (38), AGES (age, grade, ETE, and size) (39), AMES (age, metastasis, ETE, and size) (40), and MACIS (metastasis, age, completeness of resection, invasion, and size) (41). Since an active surveillance management approach or an initial surgery less than a total thyroidectomy are best reserved for patients with intrathyroidal PTC, the ability to predict the presence of ETE using diffusion weighted MRI will allow the clinician to identify patients that are likely to benefit from more aggressive initial therapy and therefore have a significant impact on clinical management, particularly in low risk thyroid cancers.…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of studies have reported a mortality rate of ≤10% (5,18). This difference may be attributable to variability in the use of treatment approaches and classification systems between studies.…”
Section: Discussionmentioning
confidence: 99%
“…WDTC neoplasms may arise from follicular cells [papillary (PTC), follicular (FTC) or Hürthle cell (HTC) carcinomas] or from parafollicular cells (medullary thyroid carcinoma) (3,4). Although WDTC accounts for <1% of all cancers, it results in >70% of mortalities from thyroid carcinomas (5).…”
Section: Introductionmentioning
confidence: 99%